National Geographic Magazine on CD ROM [ - National Geographic Society (U.S.) (Washington, D.C. : National Geographic Interactive, 1997)
Presents National Geographic on CD-ROM for the years 1888-1997
v.1. 1888-1909 -- v.2. 1910s -- v.3. 1920s -- v.4. 1930s -- v.5. 1940s -- v.6. 1950s -- v.7. 1960s -- v.8. 1970s -- v.9. 1980s -- v. 10 1990s
Title from discs. "Produced from an archive of magazines collected in a central repository and is not representative of any single regional edition of National Geographic magazine"--Container
System requirements: Windows 95 or Windows 98; Pentium 90MHz or faster processor; 24MB RAM; 70MB free hard-disk space; SVGA video card supporting 16-bit color; 16-bit sound card and speakers; 4X CD-ROM drive
System requirements: Windows 98/95/3.1; 486/33 MHz or faster; 16 MB RAM (8 MB for Windows 3.1); 32 MB free hard-disk space; SVGA card supporting 256 colours; 16 bit sound card and speakers; 2X CD-ROM drive; Optional: printer; 14,400 modem for Internet access
In English
Keywords: National geographic; Geography; Natural history